Islam: Is a cultural dialogue possible? (Revista Direito em Debate, 2022)
This article proposes a reflection on the possibility of using culture in the formation of Islamic law and on the existence of a common cultural ground that underpins human rights or, at least, work as a dialogue between the Islamic world and the western world. We analyze, through a bibliographic and documentary study, the hypothesis that culture has, in fact, reflected in the socio-historical and cultural moment of the very creation of Islam. Non-slamic critics argue that culture has influenced the formation of the Quran and sunna, thus undermining the legitimacy of Islamic law. Muslim scholars, on the other hand, argue that the Quran contains the divine word of God and that the sunna is the divinely inspired example of the prophet, so claims of cultural influence simply do not apply. As shown, this disagreement is reduced to an irresoluble circularity. The prognosis defended here is that, although there is no consensus on influence, Muslims have the necessary and sufficient methodologies to engage on a process of reformulation of classical fiqh through ijtihad to reflect political realities, contemporary legal and economic issues, especially with regard to human rights.
Keywords: Sharia. Muslim law. Cultural influence. Fiqh. Sunna.